A Novel Microplate 3D Bioprinting Platform for the Engineering of Muscle and Tendon Tissues. (December 2018) - Laternser, Sandra; Keller, Hansjoerg; Leupin, Olivier; Rausch, Martin; Graf-Hausner, Ursula; Rimann, Markus
Two-dimensional (2D) cell cultures do not reflect the in vivo situation, and thus it is important to develop predictive three-dimensional (3D) in vitro models with enhanced reliability and robustness for drug screening applications. Treatments against muscle-related diseases are becoming more prominent due to the growth of the aging population worldwide. In this study, we describe a novel drug screening platform with automated production of 3D musculoskeletal-tendon-like tissues. With 3D bioprinting, alternating layers of photo-polymerized gelatin-methacryloyl-based bioink and cell suspension tissue models were produced in a dumbbell shape onto novel postholder cell culture inserts in 24-well plates. Monocultures of human primary skeletal muscle cells and rat tenocytes were printed around and between the posts. The cells showed high viability in culture and good tissue differentiation, based on marker gene and protein expressions. Different printing patterns of bioink and cells were explored and calcium signaling with Fluo4-loaded cells while electrically stimulated was shown. Finally, controlled co-printing of tenocytes and myoblasts around and between the posts, respectively, was demonstrated followed by co-culture and co-differentiation. This screening platform combining 3D bioprinting with a novel microplate represents a promising tool to address musculoskeletal diseases.